RISE: The effectiveness of the ICQS Bukit Kayu Hitam and CIQ Sadao's 24-hour operation / Prof. Dr ROshima Said and Assoc. Prof. Dr Mohd Rizaimy Shaharudin - Said, Roshima; Shaharudin, Mohd Rizaimy (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Universiti Teknolgi MARA (Kedah) has collaborated with the Institute of Public Security Malaysia (IPSOM) to investigate the ICQS Bukit Kayu Hitam and CIQ Sadao's effectiveness as a 24-hour operation.